An Analysis of the Spelt Dehulling Process in a Cylinder Separator (Agricultural Engineering, 2023)
Spelt is one of unprofitable wheat types and requires an additional hulling process, in which the husks are removed from the grain. A device for dehulling spelt kernels was proposed. The described solution consists of a stainless-steel wire mesh cylinder with 4×20 mm and 4×30 mm longitudinal openings and a rotor with adjustable blade angles. Kernels were dehulled at the following angular speeds of the shaft: 16.76, 23.04, 29.32, 35.60, and 41.89 rad·s−1, and the following rotor blade angles: 50°, 60°, 70°, 80°, and 90°. The efficiency of glume and glumelle removal, the proportion of damaged kernels, and kernel and husk separation efficiency were evaluated during the experiment. The highest of kernel separation efficiency ηz was 81.86% using a wire mesh cylinder with 4×30 mm longitudinal openings and 81.60% for a wire mesh cylinder with 4×20 mm longitudinal openings.